Enhancing the Capacity and Stability by CoFe2O4 Modified g-C3N4 Composite for Lithium-Oxygen Batteries - Xiaoya Li; Yajun Zhao; Lei Ding; Deqiang Wang; Qi Guo; Zhiwei Li; Hao Luo; Dawei Zhang; Yan Yu (Nanomaterials, 2021)
As society progresses, the task of developing new green energy brooks no delay. Li-O2 batteries have high theoretical capacity, but are difficult to put into practical use due to problems such as high overvoltage, low charge-discharge efficiency, poor rate, and cycle performance. The development of high-efficiency catalysts to effectively solve the shortcomings of Li-O2 batteries is of great significance to finding a solution for energy problems. Herein, we design CoFe2O4/g-C3N4 composites, and combine the advantages of the g-C3N4 material with the spinel-type metal oxide material. The flaky structure of g-C3N4 accelerates the transportation of oxygen and lithium ions and inhibits the accumulation of CoFe2O4 particles. The CoFe2O4 materials accelerate the decomposition of Li2O2 and reduce electrode polarization in the charge–discharge reaction. When CoFe2O4/g-C3N4 composites are used as catalysts in Li-O2 batteries, the battery has a better discharge specific capacity of 9550 mA h g−1 (catalyst mass), and the cycle stability of the battery has been improved, which is stable for 85 cycles.